Analisis Pengetahuan Perilaku Hidup Bersih dan Sehat (PHBS) pada Anak Usia Sekolah di SMP 1 Methodist Kutalimbaru Tahun 2024 - Amirah, Nada; Azhary, Muhammad Rifqi; Sitio, Sri Sudewi Pratiwi; Tanjung, Lina Febriani; Putri, Rizqi Nanda; Damanik, Yunita Syahputri (Jurnal Penelitian Kesmasy, 2024)
Prevention of sickness, establishment of a healthy, disease-free environment, and enhancement of physical health are the goals of a clean and healthy living (PHBS) initiative in the school setting, which is a collaborative effort between students and teachers. Schools may play a crucial role in educating the public about the significance of living a healthy, clean lifestyle. The health of kids may be greatly improved by doing simple things like using soap to wash hands and eating nutritious food from the school cafeteria. In order to have a better idea of what elementary school-aged kids know about PHBS, or clean and healthy living behaviors, this study is collecting data. This study used a descriptive quantitative research strategy. Researchers at Kutalimbaru 1 Methodist Middle School in Deli Serdang Regency administered a questionnaire to students in the fall of 2023 to gauge their level of familiarity with the concept of clean and healthy living behaviors (PHBS). Thirty participants were surveyed for this research, with ten participants drawn from each of the three grade levels (Seventh, Eighth, and Ninth). According to the interview results, most students at SMP 1 Methodist Kutalimbaru have a good understanding of Clean and Healthy Living Behavior (PHBS). However, when it comes to actually practicing what they've learned, there are some big gaps. For example, 18 out of 30 students still don't wash their hands before and after eating, and 22 out of 30 students still don't eat hygienic food, which can lead to infectious diseases like diarrhea. In order to implement PHBS in school-aged children, support from parents, teachers, and school facilities is necessary. Keywords: Knowledge, Clean and Healthy Living Behavior, School Age Children